(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The use of a computer as a tool can be involved in the following forms of unlawful behaviourfinancial crimes, sale of illicit things, pornography, online gambling, intellectual property crime, e-mailspoofing, forgery, cyber defamation, and cyber stalking. Computers may also be utilised to participate inonline gambling games such as poker and blackjack. On the other hand, the computer could be a targetfor illegal activity in the following scenarios unauthorised access to the computer, computer system orcomputer networks, theft of information contained in electronic form, e-mail bombing, Salami attacks,logic bombs, Trojan attacks, Internet time thefts, web jacking, theft of computer system, and physicallydamaging the computer system. The internet has emerged as the most vital piece of physicalinfrastructure in this modern era. There has never been a time in the history of mankind and there hasnever been an innovation that has generated such great and substantial changes in the economics of theglobe, personal communication, and every sector that pertains to our age as the information age has.The internet provides instant communication between any computers that are linked to it, point-to-pointcommunication, and offers an expanding number of private and public communication options. TheInternet is a worldwide resource that connects millions of users using a standardised set of protocols.These protocols are a form of communication that is mutually agreed upon between the parties involved.